Accelerating youth agri-incubators in Africa - Lessons from Nigeria - Sudarkasa, Michael; Odetayo, Wole (Technical Centre for Agricultural and Rural Cooperation, 2019)
WeHub focuses on inspiring and empowering the youth to solve socio-economic challenges by leveraging technology